Polycystic Ovary Syndrome: Crossing the Frontiers in Management - Ahmad, Ayesha; Khan, Tamkin (International Journal of Human and Health Sciences (IJHHS), 2022)
Polycystic ovarian syndrome (PCOS) is one of the most common endocrine disorders in women with a heterogeneous clinico-pathologic spectrum characterised by varying degrees of ovulatory dysfunction and clinical and/ or biochemical features of hyperandrogenism. The etiopathogenesis of PCOS remains controversial with multiple genetic variants and environmental factors interacting together to foster development of the spectrum of clinical features. This article explores the evolving concepts of PCOS, focusing on the role of circadian rhythm and white adipose tissue; the role of precision medicine involving interplay of pharmacogenomics, nutrigenomics, chronotherapy and psychotherapy. International Journal of Human and Health Sciences Vol. 06 No. 04 Oct’22 Page: 362-371